ASSESSMENT OF HEALTH SEEKING BEHAVIOUR AMONG LAWYERS - Kausar, Dr. Rushda; Rahman, Dr. Mahmood Ur; Azam, Dr. Naila; Mahmood, Dr. Humaira; Pervaiz, Dr. Farrah (Pakistan Armed Forces Medical Journal, 2019)
Objective: To assess the health-seeking behavior among lawyers and to give viable recommendations for the improvement of their health and wellbeing Study Design: Descriptive cross-sectional. Place and Duration of Study: This study was conducted at District Bar Association, from Mar to Sep 2018. Material and Methods: Data were collected through pre-tested semi structured questionnaire distributed among a convenient sample of 323 lawyers and entered into SPSS for descriptive and inferential analyses. Results: Mean age of lawyers was 40.0 ± 8.3 with the gender distribution of Male 314 (97.2%) and Female 9 (2.8%). The 232 (71.8%) lawyers were non-smoker while 91 (28.2%) having history of smoking. Mean physical activity was 44.1 ± 24.3 minutes in a day. Health seeking behavior of lawyers 295 (91.3%) visited allopathic doctors, followed by 19 (5.9%) visiting homeopaths and 9 (2.8%) to hakims. There a sons for preferred health care provider 138 (44.1%) were reported for better health care whilst 103 (32.9%) were had faith in them, 54 (17.3%) were due to previous experience and 18 (5.8%) were not having alternative option. 18 (5.6%) were going for routine medical examination 6 monthly while 305 (94.4%) visited the facility when they get sick. Conclusion: The lawyers usually visit allopathic doctors and hospitals for the treatment. Few lawyers visit hospitals for routine medical examination, where as most of the lawyers do not prefer routine checkups.